The Influence of Intellectual Capital, GCG, and ROA on Bank Performance - Suseno; Nissa, Fachrun; Yaqin, Nurul; Budiastuti, Susanti; Guntoro (Jurnal EMT KITA, 2024)
The purpose of this study is to analyze the influence of Intellectual Capital, Good Corporate Governance (GCG), and Capital Adequacy Ratio (CAR) on financial performance. This research adopts a quantitative approach with panel data regression analysis. The theoretical foundation is established through a review of relevant literature from journal articles and books. The study utilizes numerical data derived from secondary sources, specifically financial reports obtained through the official website of the Indonesia Stock Exchange (IDX). The study population comprises Islamic commercial banks listed on the IDX from 2017 to 2022. Using a purposive sampling technique, 54 samples from 9 Islamic commercial banks were selected. Data analysis was conducted using EViews 10 software, applying the Random Effect Model (REM). The findings reveal that Intellectual Capital, GCG, and CAR significantly impact the financial performance of Islamic commercial banks listed on the IDX between 2017 and 2022. This study provides valuable insights into the financial health of banks, categorized into safe, gray, or distressed zones, thereby offering practical implications for Islamic commercial banks.
Keywords: Intellectual Capital; Good Corporate Governance; Capital Adequacy Ratio; Financial Performance; Islamic Commercial Banks